Language, Cultural Hybridity, and Resistance in K-Pop: A Linguistic Analysis of Korean Pop Music Lyrics and Performances - JIE, ZHANG (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This article examines the linguistic dynamics and cultural hybridity in Korean Pop (K-Pop) music, focusing on the role of language in lyrics and performances. With its historical roots and the expansion of Hallyu through social media, K-pop has become a transnational phenomenon. By analyzing lyrics, this study explores the linguistic hybridity and code-switching between Korean, English, and other languages as a means of self-assertion and resistance. Performances blend various cultural influences through visual aesthetics, choreography derived from global pop culture, and adaptations for international audiences. This hybrid culture is also reflected in the global fandom's lived experiences and active participation through translation and social media interaction. The discussion extends to the politics of cultural resistance within K-pop by highlighting subversive themes in lyrics that challenge societal norms, struggles for hegemony between the K-pop industry and global music markets, and issues of nationalism and political discourse. The implications of K-pop on the global music industry and society are further discussed, with references to debates over cultural appropriation versus appreciation and the possibility for cultural hybridity in other media and cultural products.